Basicity Optimization of KF/Ca-MgO Catalyst using Impregnation Method - Didi Dwi Anggoro; Luqman Buchori; Setia Budi Sasongko; Herawati Oktavianty (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
This research aimed at determining the optimum value between calcination temperature (X1), calcination time (X2) and %wt KF (X3) toward optimum basicity of KF/Ca-MgO catalyst. Approximately 2-4%wt KF was added to the KF/Ca-MgO catalyst using the impregnation method to assist the Ca-MgO, at 450-550 ºC and a calcination time of 2-4 hours. Furthermore, its basicity was analyzed using Tanabe's titration method. The use of Variance Analysis (ANOVA), indicated that calcination temperature (X1) factor achieved the highest basicity of KF/Ca-MgO catalyst, as indicated by its high F-value (16.46262) and low p-value (0.0067). The correlation between each operating variables and the responses were shown in a mathematical equation. The optimization value is estimated by limiting the calcination temperature from 415.9 to 584.1 ºC, with a calcination time ranging from 1.32 to 4.68 hours, and %wt KF of 1.3182 to 4.6818 % that obtained 1.18 mmol/g for the optimal catalyst basicity.